PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS FLIPBOOK MATERI BAGIAN TUBUH TUMBUHAN UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK - Mafdurotul Goliah; Ujang Jamaludin (Jurnal keilmuan dan Kependidikan dasar, 2023)
This study aims to determine the increase in students' understanding through the development of flipbook-based learning media on plant body parts in grade IV of elementary school. This study uses Research and Development (R&D) research using the ADDIE model which includes 4 stages: Analyze, Design, Develop, Implement, Evaluate. The type of data in this study is in the form of quantitative data and qualitative data. The data used in this study are in the form of primary data and secondary data. This research will be conducted on fourth grade students at SDN Tegal Ratu. The instruments used as product data collection tools were validation sheets by media experts, material experts, learning outcomes instrument grids, and learning outcomes instruments by experts, as well as a Likert scale. The data analysis technique is the result of the test questions (pre-test and post-test) and tested with the paired sample test in SPSS. The results of this study resulted in the feasibility and effectiveness of developing flipbook media towards increasing students' understanding of plant body parts material marked by achieving a KKM score of > 75 after using flipbook media as a learning medium.